Number talks : helping children build mental math and computation strategies, grades K-5 - Parrish, Sherry (Sausalito, CA : Math Solutions, 2010)
"This resource supports new and experienced educators who want to prepare for and design purposeful number talks for their students; the author demonstrates how to develop grade-level-specific strategies for addition, subtraction, multiplication, and division. Includes connections to national standards, a DVD, reproducibles, bibliography, and index"--Provided by publisher.
What is a classroom number talk? -- How do I prepare for number talks? -- How do I develop specific strategies in the K-2 classroom? -- How do I design purposeful number talks in the K-2 classrooms? -- How do I develop specific addition and subtraction strategies in the 3-5 classroom? -- How do I design purposeful accition and subtraction number talks in the 3-5 classroom? -- How do I develop specific multiplication and division strategies in the 3-5 classroom? -- How do I design purposeful multiplication and division number talks in the 3-5 classroom? -- What does a number talk look like at my grade level?
Includes bibliographical references (p. 383) and index.
Keywords: Arithmetic -- Study and teaching (Preschool); Arithmetic -- Study and teaching (Elementary); Thought and thinking -- Study and teaching (Preschool); Thought and thinking -- Study and teaching (Elementary)